Bilobal architecture is a requirement for calmodulin signaling to Ca(V)1.3 channels - Banerjee, Rahul (Proc Natl Acad Sci U S A, 2018)
Calmodulin (CaM) regulation of voltage-gated calcium (Ca(V)) channels is a powerful Ca(2+) feedback mechanism that adjusts Ca(2+) influx, affording rich mechanistic insights into Ca(2+) decoding. CaM possesses a dual-lobed architecture, a salient feature of the myriad Ca(2+)-sensing proteins, where two homologous lobes that recognize similar targets hint at redundant signaling mechanisms. Here, by tethering CaM lobes, we demonstrate that bilobal architecture is obligatory for signaling to Ca(V) channels. With one lobe bound, Ca(V) carboxy tail rearranges itself, resulting in a preinhibited configuration precluded from Ca(2+) feedback. Reconstitution of two lobes, even as separate molecules, relieves preinhibition and restores Ca(2+) feedback. Ca(V) channels thus detect the coincident binding of two Ca(2+)-free lobes to promote channel opening, a molecular implementation of a logical NOR operation that processes spatiotemporal Ca(2+) signals bifurcated by CaM lobes. Overall, a unified scheme of Ca(V) channel regulation by CaM now emerges, and our findings highlight the versatility of CaM to perform exquisite Ca(2+) computations.